(3QSGdI aj GdEeGeIs - (3eMeO Hf CMeO Hf Ydj Hf GdMSjf Hf GdMSfs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd QMeJg SGHbI dZVHg hHYO aEfG hbafG Ydi QSGdI ZQGA ef Sdjd GdCFeI GdgGOi ef YR GdOjf Hf GdMSf Hf CejQ GdeDefjf HjO CfgG de JUOQ Edi UOQ ef HbjI TjhN GdYJQI hbO CLHJ HLhGHjf s
(3BNQgG (B:s
(3gPG eG fYJbOg ai gPg GdeSGFd , hfYhP HGddg Cf ffUQ HGWdkG Ch fNPd MbkG Ch fJHY dZhkG Ch fbhd HZjQ HUjQI , hfNJe bhdfG Hbhdg JYGdi (B: (3bd Gddge aGWQ GdSehGJ EfJgJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejcs
(3HChdgG fbhd hbUjOI YjfjI dTeS GdOjf CMeO Hf ESeGYjd GdbQTi jQKi HgG UdGM Hf GdMSjfs
(3QSGdI jYdb eDdagG Ydi QSGdI ai GdEeGeI dYR GdOjf Hf GdMSf Hf CejQ GdeDefjf hLhGH Ydi Hf eMeO CMeO GdHcQi YdjgG s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs